PERBAIKAN YANG PERLU DILAKUKAN DALAM PENERAPAN PERSONNEL DAN CULTURAL CONTROL BERBASIS FILOSOFI KEPEMIMPINAN HASTA BRATA UNTUK MENGATASI CONTROL PROBLEM PADA PO “MAHKOTA” DI KEDIRI. - Sukma Indah Pratiwi (CALYPTRA, 2016)
This research intends to explain and predict the relationship between philosophy of leadership and informal control systems to solving control problem. this research has the goal to find out how leadership’s philosophy of Hasta Brata affect the application of informal control system. The existence of informal control system which is influenced by the philosophy of leadership that can solve the control problem. This research is applied research with a qualitative approach. This research seek to provide recommendations for control and troubleshoot problems, that need to improve implementation of the informal control system and leadership of philosophy Hasta Brata at PO "Mahkota" which has not been fully implemented. The results of this research found that there are 4 control problems that existed at the PO "Mahkota". Control problems occur due to weak control system especially informal control system. The weakness of the leadership to be one factor in the control problem. Philosophy Hasta Brata give a value added to the organizational culture and leadership so that leaders can implement more effective informal control system to solve the control problem.